The Urgency of Reformulating Corporate Criminal Liability in Tax Crimes in Indonesia - Abdul Basir (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study examines the urgency of reformulating corporate criminal liability regulations in tax crimes, which have become increasingly complex and detrimental to state finances. Although corporations have been recognized as legal subjects in various regulations, the KUP Law has not explicitly regulated the criminal liability mechanism for corporations as perpetrators of tax crimes. As a result, criminal liability is more often imposed on corporate management, while legal entities, as the main beneficiaries, are not directly held accountable. This study uses a normative juridical approach by analyzing theoretical frameworks, comparative studies, and judicial practices, including the Asian Agri case and the West Jakarta District Court’s decision. The findings show that the absence of an explicit criminal liability formulation for corporations in the KUP Law leads to weak legal certainty and reduces the effectiveness of tax law enforcement against legal entities. Therefore, it is necessary to reformulate norms that expressly establish a criminal liability mechanism for Corporate Taxpayers in the KUP Law, harmonize with the 2023 Criminal Code, and optimize the implementation of PERMA No. 13 of 2016. This reformulation is essential to build a tax system that is fair, effective, and responsive to corporate tax crime modes.